2018
DOI: 10.3390/coatings8020066
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Permeation, and Mechanical and Tribological Behavior, of CrNx Coatings Deposited at Various Bias Voltages on IN718 by Direct Current Reactive Sputtering

Abstract: In the current work, the microstructure, hydrogen permeability, and properties of chromium nitride (CrN x ) thin films deposited on the Inconel 718 superalloy using direct current reactive sputtering are investigated. The influence of the substrate bias voltage on the crystal structure, mechanical, and tribological properties before and after hydrogen exposure was studied. It was found that increasing the substrate bias voltage leads to densification of the coating. X-ray diffraction (XRD) results reveal a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Thermal stress is mainly due to the difference in the linear thermal expansion coefficient (CTE) between the substrate and the coating after deposition, resulting in a mismatch between the substrate and the coating during the postdeposition cooling. The CTE for CrN is 2.3 × 10 −6 K −1 , while the CTE for the stainless steel is much larger (around 15 × 10 −6 K −1 ) [23,25].…”
Section: Composition and Phasesmentioning
confidence: 94%
“…Thermal stress is mainly due to the difference in the linear thermal expansion coefficient (CTE) between the substrate and the coating after deposition, resulting in a mismatch between the substrate and the coating during the postdeposition cooling. The CTE for CrN is 2.3 × 10 −6 K −1 , while the CTE for the stainless steel is much larger (around 15 × 10 −6 K −1 ) [23,25].…”
Section: Composition and Phasesmentioning
confidence: 94%
“…In 2018, Kashkarov et al [ 39 ] studied CrN x coatings on Inconel 718 superalloy with respect to microstructure, hydrogen permeability and tribology. They found that a mixed cubic CrN and hexagonal Cr 2 N structure has the lowest hydrogen permeability at 873 K (500 °C) and 2 atm hydrogen pressure due to higher packing density of the cubic phase.…”
Section: Recent Advances In Hydrogen Permeation Barriersmentioning
confidence: 99%
“…Chromium nitride (CrN) coatings deposited by magnetron sputtering have been widely studied as a potential protective coating for cutting tools, dies, friction parts, etc. because of their high hardness, good wear properties and corrosion resistance [1][2][3][4][5][6][7][8][9][10][11]. The CrN x coatings deposited by conversational direct current magnetron sputtering (DCMS) generally exhibit a loose columnar structure with porosity between the columnar grains [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%